DNA metabarcoding—a new approach to fauna monitoring in mine site restoration - Fernandes, K.; van der Heyde, M.; Bunce, Michael; Dixon, Kingsley; Harris, R.; Wardell-Johnson, Grant; Nevill, Paul (Blackwell Science Inc., 2018)
Ecological restoration of landscapes is an integral part of the mining process. However, restoration is often constrained by a lack of consistent monitoring approaches. For example, the need for specialist techniques and trapping approaches often limits monitoring of fauna recovery. Application of molecular tools has made important contributions to understanding factors influencing restoration success. Here, we outline advances in next-generation sequencing methods, especially metabarcoding of environmental DNA. These have potential to revolutionize the practical contribution of genetics to the monitoring of fauna in a restoration context. DNA metabarcoding involves the simultaneous characterization of biota using DNA barcodes. It is a powerful method to assess the biodiversity contained within environmental samples (e.g. scats, bulk arthropods, soil, water, and sediment). This review outlines the challenges associated with current approaches to monitoring faunal biodiversity throughout ecological restoration. We also demonstrate how the emergence of DNA metabarcoding could recast monitoring capacity for improved ecological restoration outcomes, while discussing current limitations of a DNA-based approach to biodiversity assessment.